Drug metabolism in the elderly: A multifactorial problem?. (June 2017) - Waring, R.H.; Harris, R.M.; Mitchell, S.C.
Highlights: Drug metabolism in healthy old age is similar to that found in young adults. Drug metabolism may be reduced in elderly subjects who are frail and/or ill. Adverse drug reactions in elderly patients are not predictable on current models. Abstract: Whether or not an individual's drug metabolising capacity declines with advancing age is a vexing question. There is no clear evidence that drug metabolism itself ('the biologically-assisted chemical alteration of the administered parent molecule') is less efficient in healthy old age than at younger ages, whereas a decreased capacity may be associated with ill-health and frailty. However, elderly individuals do show a reduced enzyme induction capability and are less able to tolerate overdoses. It appears that the majority of deleterious clinical outcomes related to drug therapy in an elderly (usually ill or frail) population may be ascribed to various anatomical and physiological age-related changes. These may affect both pharmacodynamics and pharmacokinetics, but not necessarily drug metabolism. Information gleaned from animal studies undertaken mainly in rodents does not seem to be of relevance to humans and studies in healthy aged human populations may not highlight possible problems. However, certain circumstances may influence metabolic competence, and phenotyping rather than genotyping is of more value in identifying those susceptible to adverse drug reactions. This short review discusses the potential contributions of four factors (inflammation, circadian rhythm, gut microbes, epigenetic aspects) which may lead to alterations in drug metabolism with increasing age.